Refractory Convulsive Status Epilepticus in Children: Etiology, Associated Risk Factors and Outcome - BARZEGAR, Mohammad; MAHDAVI, Mohammad; GALEGOLAB BEHBEHANI, Afshin; TABRIZI, Aidin (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Barzegar M, Mahdavi M, Zalegolab behbehani A, Tabrizi A. Refractory Convulsive Status Epilepticus in Children: Etiology, Associated Risk Factors and Outcome. Iran J Child Neurol. Autumn 2015;9(4): 24-31. Abstract Objective Refractory status epilepticus (RSE) is a life-threatening disease in children wherein the patient’s convulsive seizures do not respond to adequate initial anticonvulsants. RSE is associated with high rate of mortality and morbidity. This study was aimed to survey the risk factors leading status epilepticus (SE) to RSE in children, and their early outcome. Materials & Methods Patients with SE hospitalized in Tabriz Children’s Hospital, Iran were studied during the years 2007 and 2008 with regard to their clinical profile, etiology, the treatment methods available to them and their outcome upon release from the hospital. Results Among 132 patients with SE, 53 patients (40.15%) suffered from RSE. Acute symptomatic etiology was a risk factor responsible for developing RSE in the patient (P=0.004). Encephalitis was the most common etiology of acute symptomatic SE. There was no significant relationship observed between RSE and the patients’ age, gender, date of initial drug intake and type of seizure. The mortality rate was 8.3% and a new neurological deficit occurred in 25.7% of cases. None of RSE with encephalitis returned to the baseline status. Mortality and morbidity rates were significantly higher in children with RSE than in those with SE (P=0.006). Conclusion Etiology of SE significantly influenced prognosis of it with significant incidence of RSE in acute symptomatic group. Because acute neurological insult such as encephalitis and meningitis are common causes of RSE in children, properly management of them is necessary to avoid permanent brain damage.